2000
DOI: 10.1093/brain/123.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Selective right parietal lobe activation during mental rotation

Abstract: Regional cerebral blood flow (rCBF) was measured with PET in seven healthy subjects while they carried out a mental rotation task in which they decided whether alphanumeric characters presented in different orientations were in their canonical form or mirror-reversed. Consistent with previous findings, subjects took proportionally longer to respond as characters were rotated further from the upright, indicating that they were mentally rotating the characters to the upright position before making a decision. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
186
0
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(228 citation statements)
references
References 59 publications
32
186
0
10
Order By: Relevance
“…Post-hoc tests were conducted using Tukey's HSD procedure and partial eta squared (η 2 ) was calculated to determine effect size. To analyse RT and accuracy overall, a commonly used technique in mental rotation studies to increase reliability of estimates by increasing the number of trials at each angle was employed (see, for example, Harris, et al, 2000;Roelofs, van Galen, Keijsers, & Hoogduin, 2002). This involved combining data from the same angular rotation, regardless of direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-hoc tests were conducted using Tukey's HSD procedure and partial eta squared (η 2 ) was calculated to determine effect size. To analyse RT and accuracy overall, a commonly used technique in mental rotation studies to increase reliability of estimates by increasing the number of trials at each angle was employed (see, for example, Harris, et al, 2000;Roelofs, van Galen, Keijsers, & Hoogduin, 2002). This involved combining data from the same angular rotation, regardless of direction.…”
Section: Discussionmentioning
confidence: 99%
“…combining responses to 45 and 315 ) to allow sufficient responses at each angle for analysis. This is a common technique when analysing such data (Harris, et al, 2000;Roelofs, et al, 2002;Williams, Thomas, Maruff, Butson, & Wilson, 2006). However, this technique could be criticised given our findings that responses to left and right hands differed when presented in CW compared to CCW directions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally agreed that the parietal cortex is involved in the mental rotation process, there is considerable disagreement about interhemispheric activation differences. For Shepard-Metzler-like stimuli most studies have reported bilateral parietal activation (Cohen et al, 1996;Richter et al, 1997Richter et al, , 2000Jordan et al, 2001), while experiments using other stimuli demonstrated predominance of either the left (Alivisatos and Petrides, 1997) or the right hemisphere (Harris et al, 2000;Yoshino et al, 2000) or no distinct difference (Tagaris et al, 1998;Lamm et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…From these results it was hypothesized that subjects "mentally rotated" the mental image of one object along a trajectory until it had the same orientation as the other object and then compared both for congruency. Based on this study, a number of experiments investigating the brain responses underlying mental rotation processes have been performed, using electrophysiological methods, positron emission tomography and functional magnetic resonance imaging (fMRI) (Cohen et al, 1996;Alivisatos and Petrides, 1997;Tagaris et al, 1997Tagaris et al, , 1998Richter et al, 1997Richter et al, , 2000Kosslyn et al, 1998;Carpenter et al, 1999;Harris et al, 2000;Yoshino et al, 2000;Jordan et al, 2001;Lamm et al, 2001;Vingerhoets et al, 2001Vingerhoets et al, , 2002. Although it is generally agreed that the parietal cortex is involved in the mental rotation process, there is considerable disagreement about interhemispheric activation differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation